EVALUATION OF THE IMPLEMENTATION OF CASHLESS PAYMENTS AS A MEASURE TO PREVENT ILLEGAL FEES IN CLASS IIB CORRECTIONAL INSTITUTIONS IN SLEMAN - Wily Nur Fauzi Pratama; Naniek Pangestuti (Universitas Nusa Cendana, 2026)
This study aims to evaluate the implementation of a cashless system as an effort to prevent illegal fees at Class IIB Sleman Correctional Institution. The research applies a descriptive qualitative approach, with data collected through interviews, observations, and documentation studies. The analysis is based on the policy implementation theory of Randall B. Ripley and Grace A. Franklin, which emphasizes two perspectives: compliance with established policies and an examination of what occurs during implementation and the factors influencing it. The findings show that the implementation of the cashless system helps improve transparency and efficiency in financial transactions among inmates. However, its effectiveness is still constrained by several factors, including technical issues, overcrowding conditions, limited human resources, and misconduct by certain staff members. Although the implementers generally demonstrate a good level of compliance and understanding of the policy, these obstacles hinder the system from functioning optimally. The study is limited because it focuses only on one correctional institution and does not explore inmates’ perceptions in depth. Therefore, future research is recommended to examine the role of digital monitoring systems and expand the research scope to other correctional institutions. Keywords: Cashless System; Illegal Fees; Policy Evaluation